THE THE EFFECT OF CAREER DEVELOPMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT PT. TRI GLOBAL PRATAMA IN MAKASSAR CITY: PENGARUH PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. TRI GLOBAL PRATAMA DI KOTA MAKASSAR - Sari, Nadia Indah; nuraenigani (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
ABSTRACT This study aims to determine the effect of career development and work motivation on employee performance at PT. Tri Global Pratama in Makassar City. The variables used in this study are career development and work motivation as independent variables and employee performance as dependent variables. This study is a quantitative study. The data source in this study is primary data where the data collection method uses a questionnaire method distributed to employees of PT. Tri Global Pratama in Makassar City, as well as secondary data through documents related to the variables studied. The number of samples used was 21 respondents. The data analysis technique in this study used Structural Equation Modeling (SEM) using the help of SmartPLS version 4.0 for windows. The results of this study explain that career development and work motivation simultaneously have a significant positive effect on employee performance, career development has a significant positive effect on employee performance, and work motivation does not affect employee performance.